The double-edged scalpel: Experiences and perceptions of pregnancy and parenthood during Canadian surgical residency training. - Mikaela J Peters; Alissa W Zhang; Darren M Roffey; Kelly A Lefaivre (PLoS ONE)
Introduction Only 34% of Canadian surgeons in 2022 were female. The protracted length of surgical residency training, concerns regarding infertility, and increased rates of obstetrical complications have been shown to contribute to the disproportionate lack of females in surgical specialties. Methods A novel online survey was sent to all surgical residents in Canada. Respondents were asked about perceptions of pregnancy and parenthood during surgical training, and parents were asked about parental leave, accommodations they received, and pregnancy complications. Chi squared tests were used to compare opinions of male and female residents. Results A total of 272/2,419 (11.2%) responses were obtained, with a high response from females (61.8%) and orthopaedic residents (29.0%). There were 56 women reporting 76 pregnancy events during training, 62.5% of which had complications. Notably, 27.3% of men and 86.7% of women 'agreed' or 'strongly agreed' that surgeons have higher pregnancy complication rates than the general population (p<0.001). Men were much less likely to believe that pregnant residents should be offered modified duties (74.2% of men, 90.0% of women, p = 0.003). Women were much more likely to experience significant stigma or bias due to their status as a parent (43% of women, 0% of men, p<0.001). Women reported negative comments from others at a higher rate (58.5% of women, 40.7% of men, p = 0.013). Women believe there is negative stigma attached to being pregnant during training (62.7% of women, 42.7% of men, p = 0.01). The limitations of our study include a small sample size and response bias. Conclusion Challenges and negative perceptions exist around pregnancy and parenthood in surgical residency, which disproportionately affect women trainees.